2019
DOI: 10.1016/j.jth.2019.100607
|View full text |Cite
|
Sign up to set email alerts
|

Commute patterns and depression: Evidence from eleven Latin American cities

Abstract: IntroductionAlthough travel behavior is expected to influence personal health, few studies have examined associations with mental health. This study examines associations between commute patterns and mental health using survey data in 11 Latin American cities.MethodsUsing a survey conducted by the Development Bank of Latin America in 2016, we measured the presence of depressive symptoms using the 10-item Center for Epidemiologic Studies Depression (CESD-10) screening scale. We used multilevel non-linear models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 49 publications
(59 reference statements)
2
35
1
2
Order By: Relevance
“…The lack of a significant relationship between active commuting and depression symptoms in these articles are in agreement with previous studies among men and women, which showed that walking distance was not related to depression symptoms [32][33][34]. For those who use an active mode of transportation, transit connectivity matters more for mental health than active travel [26,34]. Furthermore, there is a difference between walking and cycling as a mode of active transportation.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The lack of a significant relationship between active commuting and depression symptoms in these articles are in agreement with previous studies among men and women, which showed that walking distance was not related to depression symptoms [32][33][34]. For those who use an active mode of transportation, transit connectivity matters more for mental health than active travel [26,34]. Furthermore, there is a difference between walking and cycling as a mode of active transportation.…”
Section: Discussionsupporting
confidence: 90%
“…Cross-sectional evidence from two studies showed that the association between active commuting and depression is not consistent. In one study, performed among Latin American adults, it was found that non-motorised modes of travel were not associated with depression [26]. On the other hand, a study among African-American adults reported that, while women who reported walking often presented a lower probability for depressive symptoms than women who reported never walking, the same pattern was not observed in men [23].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations